La valeur de l'enseignement du droit et ses valeurs - Verge, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Law teaching is far from aseptic. Professional objectives and attitudes currently enhance values that are inherent to the legal system and are well received in the juridical community to which students aspire to belong. Does it devolve on the teacher of law to question legal rules and institutions beyond their normative coherence ?